2014
DOI: 10.4161/21645515.2014.970973
|View full text |Cite
|
Sign up to set email alerts
|

Expression of HPV-16 L1 capsomeres with glutathione-S-transferase as a fusion protein in tobacco plastids: An approach for a capsomere-based HPV vaccine

Abstract: Human Papillomavirus (HPV) is the main cause of cervical cancer, which is the second most severe cancer of women worldwide, particularly in developing countries. Although vaccines against HPV infection are commercially available, they are neither affordable nor accessible to women in low income countries e.g. Africa. Thus, alternative cost-effective vaccine production approaches need to be developed. This study uses tobacco plants to express pentameric capsomeres of HPV that have been reported to generate elev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Schädlich and colleagues reported that the L1ΔN10 protein was particularly immunologic and that L1 constructs could be administered to produce potent immunogenic responses to capsomeres in bacteria as a potentially inexpensive alternative to VLP-based formulations. Furthermore, in another study, tobacco plants were used to express pentameric capsomeres of a modified HPV-16 L1 (L1-2xCysM) protein to induce immunity against HPV ( 146 ). Licensing of subunit vaccine (VLP-based) from the L1 protein (plus adjuvant) has been done already ( 147 ).…”
Section: Hpv Diseasementioning
confidence: 99%
“…Schädlich and colleagues reported that the L1ΔN10 protein was particularly immunologic and that L1 constructs could be administered to produce potent immunogenic responses to capsomeres in bacteria as a potentially inexpensive alternative to VLP-based formulations. Furthermore, in another study, tobacco plants were used to express pentameric capsomeres of a modified HPV-16 L1 (L1-2xCysM) protein to induce immunity against HPV ( 146 ). Licensing of subunit vaccine (VLP-based) from the L1 protein (plus adjuvant) has been done already ( 147 ).…”
Section: Hpv Diseasementioning
confidence: 99%
“…For example, cholera nontoxic B subunit (CNTB)-fused native human blood-clotting factor VIII heavy chain (FVIII HC;86.4 kD) or ANGIOTENSIN CONVERTING ENZYME2 (92.5 kD) were expressed at very low levels (Shenoy et al, 2014;Sherman et al, 2014). Likewise, the expression of viral vaccine antigens is quite unpredictable, with high, moderate, or extremely low expression levels (Birch-Machin et al, 2004;Lenzi et al, 2008;Waheed et al, 2011aWaheed et al, , 2011bInka Borchers et al, 2012;Hassan et al, 2014). Furthermore, viral antigens are highly unstable, with expression observed in youngest leaves but not in mature leaves (McCabe et al, 2008).…”
mentioning
confidence: 99%
“…In addition, an HPV-16L1 produced in tomato and tobacco plants were able to elicit humoral and cytotoxic T-cell epitope activity in mice (De la Rosa et al, 2009;Šmídková et al, 2010). The expression of HPV-16L1 capsomeres with glutathione-S-transferase as a fusion protein in tobacco chloroplasts has been reported to generate elevated immune responses against HPV (Hassan et al, 2014). The production of human β-glucocerebrosidase in Nicotiana benthamiana for the replacement therapy of rare diseases is also reported (Naphatsamon et al, 2018).…”
Section: Discussionmentioning
confidence: 99%